Competitive Strategy for Wooden Pallet Packaging Products Using Porter's Five Forces Analysis (Case Study on CV. Karya Anugerah Sentosa) - Maurina, Annisa Cindy; Rusdianto, R. Yuniardi (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the business world, competition between companies is very sharp, where new competitors can enter easily and suppliers and customers can increase their bargaining. With this research, it can be seen what strategies CV. Karya Anugerah Sentosa, the competitive climate of wooden pallet packaging manufacturing companies using Porter's Five Force theory and alternative strategies used. This type of research is descriptive qualitative research. The research subject is CV. Karya Anugerah Sentosa with the research object of Porter's five powers. The respondents used were one owner, one person in charge of the warehouse, four warehouse employees and seven consumers from different companies. The results of this research show that the strategies used to deal with Porter's five forces are differentiation strategies and diversification strategies.